The Dynamics of Identity Politics Management In The Tanimbar Islands Regency - Simon Batmomolin; Tonny D. Pariela; Tontji Soumokil (Westscience Press, 2023)
Following the reform era, Indonesia faces the challenge of the widespread emergence of identity politics that prioritizes certain groups or symbols to gain political influence. If left unaddressed, this phenomenon could disrupt national resilience and the quality of democracy in Indonesia. This research aims to analyze the dynamics of identity politics in the Tanimbar Islands Regency, Maluku Province, and to find solutions so that identity politics can lead to goodness, in accordance with values and culture, thereby achieving stability in society. The research methodology involves a literature review or literature study as the primary approach. This method entails in-depth analysis of various literature sources relevant to the research topic, aiming to provide a comprehensive overview of current issues, conceptual frameworks, and approaches taken by previous studies. The results of this research reveal that the management of identity politics in the Tanimbar Islands Regency has been organized and become a shared interest. The community sees identity politics as a means to facilitate the interests of groups, ethnicities, religions, and collective interests, allowing peace to be achieved, and government policies to be implemented fairly and equally.